Improved Graphitic Structure of Continuous Carbon Nanofibers via Graphene Oxide Templating. (19th June 2013) - Papkov, Dimitry; Goponenko, Alexander; Compton, Owen C.; An, Zhi; Moravsky, Alexander; Li, Xing‐Zhong; Nguyen, SonBinh T.; Dzenis, Yuris A.
Abstract Continuous carbon nanofibers (CNF) present an attractive building block for a variety of multifunctional materials and devices. However, the carbonization of poly(acrylonitrile) (PAN) precursors usually results in CNFs with poor graphitic structure and, consequently, modest/non‐optimized properties. This paper reports that the graphitic structure of CNFs can be improved with an addition of a small amount of graphene oxide into PAN prior to processing. Continuous CNFs with 1.4 wt% of graphene oxide nanoparticles are prepared from PAN solutions by electrospinning, stabilized, and carbonized at 800 °C, 1200 °C, and 1850 °C. While the as‐prepared graphene oxide‐filled PAN nanofibers exhibit a considerable reduction in polymer crystallinity, Raman analysis of the carbonized nanofibers shows that both templating with graphene oxide and increasing the carbonization temperature significantly improve the graphitic order in CNFs. The effect of graphene oxide is more significant at higher carbonization temperatures. Selected area electron diffraction analysis of individual nanofibers reveals increased graphitic order and preferred orientation both in the vicinity of visible graphene oxide nanoparticles and in the regions where nanoparticles were not visible. These results indicate a possibility of global templating in CNFs, where the addition of a small amount of graphene oxide nanoparticles can template the formation of good, preferentially oriented graphitic crystallites in CNFs, leading to improved structure and mechanical and transport properties.